IMPACT OF EROSION ON MOUNTAIN FOREST SOILS IN THE ZONE OF MIXED SPRUCE FORESTS OF THE UKRAINIAN CARPATHIANS AND ANTI-EROSION MEASURES ON LOGGING SITES - Korinets , Ю.; Snitynskyi , В.; Khirivskyi , П.; Panas , Н.; Sapeliuk , С. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The study offers a thorough characterization of the erosion processes occurring in mountain forest soils within the mixed spruce forest zone, examining their dependence on various natural and anthropogenic factors. It identifies the types and specific characteristics of erosion resulting from logging activities and assesses the properties of brown forest soils in the Carpathian region. The extent and volume of soil loss due to these erosion processes have been quantified. The paper provides insights into the varying influence of slope steepness on erosion intensity and estimates the quantity of fine soil particles transported by subsurface runoff. It was found that the studied areas exhibit significant differences in the degree of soil loss, which results from both mechanical disruption and subsequent water erosion. A notable feature of logged areas is the intensification of erosion from the upper to the lower parts of the slope. Soil displacement and sediment deposition at logging sites predominantly occur under the influence of mechanical forces related to initial timber transportation. In comparison to control plots, marked compaction of the topsoil and a reduction in its porosity were observed in clear-cut areas. The physical properties of the soil are directly correlated with the level of disturbance to the upper soil layer. Mechanical impacts during tree felling and transportation significantly impair the hydrophysical characteristics of soils on slopes, leading to increased surface runoff and enhanced water erosion. The decline in the physical and chemical condition of soils on eroded logging sites adversely affects their capacity for forest growth. This poses substantial challenges for artificial reforestation and diminishes the growth rates and quality of subsequent forest generations. To mitigate the adverse effects of erosion, a system of anti-erosion measures has been proposed for implementation in logged areas.